DNA glycosylase Neil3 regulates vascular smooth muscle cell biology during atherosclerosis development. (May 2021) - Quiles-Jiménez, Ana; Gregersen, Ida; Segers, Filip M.; Skarpengland, Tonje; Kroustallaki, Penelope; Yang, Kuan; Kong, Xiang Yi; Lauritzen, Knut H.; Olsen, Maria B.; Karlsen, Tom Rune; Nyman, Tuula A.; Sagen, Ellen L.; et al.
Abstract: Background and aims: Atherogenesis involves a complex interaction between immune cells and lipids, processes greatly influenced by the vascular smooth muscle cell (VSMC) phenotype. The DNA glycosylase NEIL3 has previously been shown to have a role in atherogenesis, though whether this is due to its ability to repair DNA damage or to other non-canonical functions is not yet clear. Hereby, we investigate the role of NEIL3 in atherogenesis, specifically in VSMC phenotypic modulation, which is critical in plaque formation and stability. Methods: Chow diet-fed atherosclerosis-prone Apoe −/− mice deficient in Neil3, and NEIL3-abrogated human primary aortic VSMCs were characterized by qPCR, and immunohistochemical and enzymatic-based assays; moreover, single-cell RNA sequencing, mRNA sequencing, and proteomics were used to map the molecular effects of Neil3/NEIL3 deficiency in the aortic VSMC phenotype. Furthermore, BrdU-based proliferation assays and Western blot were performed to elucidate the involvement of the Akt signaling pathway in the transdifferentiation of aortic VSMCs lacking Neil3/NEIL3. Results: We show that Neil3 deficiency increases atherosclerotic plaque development without affecting systemic lipids. This observation was associated with a shift in VSMC phenotype towards a proliferating, lipid-accumulating and secretory macrophage-like cell phenotype, without changes in DNA damage. VSMC transdifferentiation in Neil3-deficient mice encompassed increased activity of the Akt signaling pathway, supported by cell experiments showing Akt-dependent proliferation in NEIL3-abrogated human primary aortic VSMCs. Conclusions: Our findings show that Neil3 deficiency promotes atherosclerosis development through non-canonical mechanisms affecting VSMC phenotype involving activation of the Akt signaling pathway. Graphical abstract: Image 1 Highlights: Apoe −/− /Neil3 −/− mice develop more atherosclerosis as compared to Apoe −/− mice. Apoe −/− /Neil3 −/− mice display increased medial VSMC area and layer disorganization. Increased aortic VSMC proliferation in Apoe −/− /Neil3 −/− mice and NEIL3-deficient primary human VSMCs. Neil3 deficiency increases aortic VSMC phenotypic transdifferentiation towards an atherosclerotic macrophage-like cells. Neil3/NEIL3 deficiency-dependent VSMC proliferation involves activation of the Akt signaling pathway.